Triggering method in assisted reproduction alters the cumulus cell transcriptome. Issue 2 (August 2019) - Fuchs Weizman, Noga; Wyse, Brandon A; Gat, Itai; Balakier, Hanna; Sangaralingam, Mugundhine; Caballero, Julieta; Kenigsberg, Shlomit; Librach, Clifford L.
Abstract: Research question: How does the choice of triggering final oocyte maturation affect the cumulus cell transcriptome? Design: Sixty patients undergoing gonadotrophin-releasing hormone antagonist (GnRH-ant) IVF cycles were recruited for this nested case–control study. Patients were stratified into three subgroups based on their ovarian reserve (high, normal and low). Triggering final oocyte maturation was accomplished by either single trigger (with human chorionic gonadotrophin [HCG] only or gonadotrophin-releasing hormone agonist [GnRH-ag] only) or dual trigger combining HCG and GnRH-ag. The choice of trigger was at the discretion of the treating physician. Within each group patients receiving a dual trigger were matched by demographic and pre-stimulation parameters with patients receiving a single trigger. The matching was performed to minimize the biological variability within each subgroup. Thirty patients were included in the final analysis. Cumulus cells were stripped away from the retrieved oocytes. Cumulus cells from three sibling oocytes were pooled, the RNA extracted and libraries prepared. Next-generation sequencing was performed on all samples. Results: Dual triggering supports key ovarian pathways of oocyte maturation and extracellular matrix remodelling, while attenuating vasculo-endothelial growth and providing antioxidant protection to the growing follicles. Conclusions: This is the first study to delineate key transcriptomic changes under dual triggering of final oocyte maturation, across different patient populations. The findings underline the need for larger-scale studies validating transcriptomic effects of methods for triggering final oocyte maturation. Furthermore, there is a need for large-scale clinical randomized controlled studies to relate the findings of this study with clinical outcomes.